Cross-Cultural Communication Between Pakpak Simsim and Pakpak Boang - Dewi Dokate Manalu; Syahrul Abidin (UNIVERSITAS PAKUAN, 2023)
This study aims to determine cross-cultural communication between pakpak simsim and pakpak boang, factors of language differences in communication, clan identity factors, cultural customs of pakpak Simsim and pakpak Boang. as well as communication in customs and traditions. Similarities in language or communication are used by both, but what distinguishes them is the dialect as in the mention of the letter